(untitled) (Orfeu, 2025)
The Mini-Suite of University Survival: From Choro to Vacation is a musical creation project carried out with support from the BIPAC/UTFPR public cultural funding program. The proposal consisted of composing four original instrumental pieces, fully notated for hybrid ensembles involving 8-string classical guitar (or viola caipira), violin, and transverse flute. The project explores the concept of border music through its institutional context—a technological university with no formal music programs—and its aesthetic approach, which combines Brazilian popular genres (choro, forró, waltz) with experimental and collaborative composition practices for chamber music. In this article, we present how the project was developed and offer a brief investigation into how the instruments used in the suite are positioned within the sociocultural context of border music in Brazil.